Strengthening Christian Leadership And Faith Militance Through The Christian Leadership Training Program (LKK) For Catholic Students - Reno Francius Simanullang; Barita Esman; Charles Junaidi Gea; Ririn Permatasari Gaurifa (PT. TAROMBO RESEARCH DEVELOPMENT, 2026)
This community service activity aims to strengthen Christian leadership, increase faith militancy, develop organizational skills, and increase students' social sensitivity through the Christian Leadership Training (LKK) program. The activity was carried out over five days using a participatory approach based on adult education (andragogy). The methods used included interactive lectures, group discussions, reflection, meditation, simulations, debate and trial practice, intensive mentoring, and Eucharistic celebrations. Evaluation was carried out through participatory observation, daily reflection, assignment assessments, and evaluative discussions. The results of the activity showed that participants experienced an increased understanding of self-identity, Christian spirituality, servant leadership, organizational skills, and sensitivity to various social issues. Furthermore, this activity successfully improved participants' communication, collaboration, organizational leadership, and constructive conflict resolution skills